PRESERVING RIAU MALAY ALLUSIONS: A LINGUISTIC APPROACH TO CHARACTER EDUCATION - Marni, Silvia; Pernantah, Piki Setri; Hermandra, Hermandra; Sakilah, Sakilah; Rahmat, Wahyudi; Tiawati R, Refa Lina (JURNAL KONFIKS, 2025)
Riau Malay is a vital part of Indonesia’s oral heritage, reflecting the socio-cultural identity of the Riau Malay community. In everyday interactions, Riau Malays frequently use allusive language as a means of politeness and as a reflection of cultural values. These linguistic expressions facilitate respectful communication and serve as a tool for character education. This study aims to redefine the role of Riau Malay figurative expressions as more than just linguistic tools, but as fundamental components of politeness and ethical communication. Additionally, it examines how these linguistic traditions can be preserved and integrated into higher education to foster character development, particularly in instilling values such as integrity, empathy, and respect among university students. A qualitative descriptive approach was used to analyze figurative expressions in Riau Malay. Data collection included documentation of traditional linguistic expressions and interviews with cultural experts and educators. The analysis focused on the role of allusions in social interactions and their contribution to shaping ethical behavior. Findings reveal that Riau Malay allusions are deeply embedded in cultural communication, serving as markers of politeness and carriers of moral and ethical values. These expressions reflect virtues such as humility, respect, and social harmony, reinforcing positive character traits among speakers. Incorporating Riau Malay figurative language into higher education has shown potential in strengthening students' cultural identity and ethical behavior. Interviews with educators revealed that students who engage with Malay linguistic traditions develop a deeper appreciation for local wisdom and improve their interpersonal communication skills. This study underscores the importance of preserving and promoting Riau Malay allusions as a means of fostering character education in higher learning institutions. By integrating these expressions into academic discourse, universities contribute to cultural heritage preservation while instilling ethical values in students. Future research should explore the long-term impact of structured linguistic programs on moral development and identify further ways to integrate traditional linguistic wisdom into modern educational frameworks.